2015
DOI: 10.1038/ng.3427
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent inactivating RASA2 mutations in melanoma

Abstract: Analysis of 501 melanoma exomes revealed RASA2, encoding a RasGAP, as a tumor-suppressor gene mutated in 5% of melanomas. Recurrent loss-of-function mutations in RASA2 were found to increase RAS activation, melanoma cell growth and migration. RASA2 expression was lost in ≥30% of human melanomas and was associated with reduced patient survival. These findings reveal RASA2 inactivation as a melanoma driver and highlight the importance of Ras GAPs in cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 24 publications
(35 reference statements)
4
78
1
Order By: Relevance
“…We have shown recently that PDX derived from BRAF inhibitor relapsed patients and expanded on chronic therapy could be used to identify effective second line combination therapies based on genomic and proteomic profiling (Krepler et al, 2016). While these studies demonstrate the feasibility of the PDX approach, the melanoma TCGA and other studies (Arafeh et al, 2015; Cancer Genome Atlas, 2015; Krauthammer et al, 2015) highlight the pronounced heterogeneity of this cancer type. Both concepts are combined here in an unparalleled collection of 459 mutationally and clinically diverse melanoma PDX and live frozen tissues, providing an exhaustive and testable resource for the melanoma research field.…”
Section: Introductionmentioning
confidence: 72%
“…We have shown recently that PDX derived from BRAF inhibitor relapsed patients and expanded on chronic therapy could be used to identify effective second line combination therapies based on genomic and proteomic profiling (Krepler et al, 2016). While these studies demonstrate the feasibility of the PDX approach, the melanoma TCGA and other studies (Arafeh et al, 2015; Cancer Genome Atlas, 2015; Krauthammer et al, 2015) highlight the pronounced heterogeneity of this cancer type. Both concepts are combined here in an unparalleled collection of 459 mutationally and clinically diverse melanoma PDX and live frozen tissues, providing an exhaustive and testable resource for the melanoma research field.…”
Section: Introductionmentioning
confidence: 72%
“…Using the most stringent approaches to distinguish driver versus passenger mutations by the InVEx procedure [29], TCGA analysis identified 13 core genes (BRAF, NRAS, TP53, NF1, CDKN2A, ARID2, PTEN, PPP6C, RAC1, IDH1, DDX3X, MAP2K1, and RB1) of which IDH1 and DDX3X were the only novel significant genes identified by this study. Two subsequent whole-exome studies in melanoma identified loss of function mutations in RASA2, encoding a GTPase activating protein for RAS, in 4% of cutaneous melanomas, suggesting its role as a key driver gene in melanoma and particularly in NF1-mutated tumors [32,44]. RASA2 mutations result in RAS activation, leading to increased proliferation and migration of melanoma cells and poorer overall survival of stage III melanoma patients [44].…”
Section: Novel Driver Genes Revealed By Genomic Approachesmentioning
confidence: 98%
“…Two subsequent whole-exome studies in melanoma identified loss of function mutations in RASA2, encoding a GTPase activating protein for RAS, in 4% of cutaneous melanomas, suggesting its role as a key driver gene in melanoma and particularly in NF1-mutated tumors [32,44]. RASA2 mutations result in RAS activation, leading to increased proliferation and migration of melanoma cells and poorer overall survival of stage III melanoma patients [44]. The prognostic significance of most of these newly identified driver genes in cutaneous melanoma is still largely unknown, and need to be explored.…”
Section: Novel Driver Genes Revealed By Genomic Approachesmentioning
confidence: 99%
“…NF1 encodes Neurofibromin 1, a Ras-GAP, that switches the Ras protein from its active GTP-bound state into its inactive GDPbound state, thereby turning off MAPK signalling promoted proliferation 45 . Inactivating NF1 mutations are found at high frequency not only in Neurofibromatosis 1 46 but also in a variety of cancers like melanoma 47,48 , glioblastoma 49,50 and ovarian cancer 51 . We first confirmed by qRT-PCR that SPRED2 mRNA levels following CRISPRa mediated gene activation were almost identical in K562 cells with or without NF1 (Fig.…”
Section: Spred2 Sensitises Cells Through Nf1mentioning
confidence: 99%